The Development Of Social Influence And Aesthetic On Purchase Intention - Alberta Honylia Novitasari Sambe; Jony Oktavian Haryanto (Jurnal Manajemen, 2022)
Due to the development of the internet nowadays, people utilize it with games and it results in the development of gaming industries that leads to the strong existence of the virtual economy. However, the development of the gaming industry in Indonesia was indeed a little late compared to other countries. This study generates a new perspective that describes purchase intention on virtual goods in Massively Multiplayer Online Social Games (MMOSG), Audition, in Indonesia. This research is done through a survey by using a questionnaire that acquired 200 Audition players as respondents. The data processing used is structural equation modelling. Results of the study show factors that significantly influence purchase intention on virtual goods are social influence and aesthetics in which purchase intention affects actual purchase behaviour, while price utility and satisfaction do not influence purchase intention.